Investigation of Relation between Tax Laws and Regulations and Tax Evasion - Ghanbari, Mehrdad; Nouri, Zahra; Mahdavi, Mahnaz; Nezhad, Mahin Absalan; Azizi, Zahra; Moghadam, Akhtar Derikvand (International Review of Management and Marketing, 2018)
The main purpose of this research is considered of performance techniques for competent of tax system in country. Base of this research, this question will discusses why the tax system in country is ineffective? Although several answers bear in mind for this question for people and most of tax agents, but as a researcher, they attempt to find a strict and scientific answer for aforesaid question. In this study, statistics community consists of 250 persons of tax agents and payers in ILAM province. In this article they use of library and field approach. The information provided by questionary. They examine the investigations assumptions with use of 35 questions involving 4 choices. The validity of questionary questions is evaluated by ALFA test ( . probably, we can plan for competent of tax system based on given results There is a significant direct relationship between tax regulations and tax evasion. Further, there is a significant direct relationship between tax system efficiency and tax evasion tricks. Results of the present study suggest that any change, though small, in the body of tax rules and regulations would equally affect tax evasion, whether it is positive or negative. Keywords: tax, tax payers, tax obedience, self-comment, tax evasion. JEL Classification: H2